Influence of the heating rate on the thermodegradation during the mild pyrolysis of the wood. Issue 2 (4th March 2023) - Pétrissans, Anelie; Lin, Yu-Ying; Nguyen, Tram N.; Colin, Baptiste; Quirino, Rafael L.; Rios-Teixeira, Priscila; Chen, Wei-Hsin; Pétrissans, Mathieu
ABSTRACT: Wood constitutes a renewable and sustainable material, which raw utilization is limited because of the weak durability and dimensional instability. To improve shortcomings, a mild pyrolysis in the temperature range 200–300°C in oxygen-free atmosphere has been used for years. However, a significant lack of knowledge persists in the initial stage of the process. The purpose of this study is to investigate the influence of the heating rate on the wood thermodegradation pathway and the impact of this parameter on the conferred properties. The heating rate influences the total duration of the process and is strongly related to the power capacity of the heater. Experiments of thermal degradation were carried out at two different scales. Thermogravimetric analysis on wood powder allows to better understand the degradation scheme of biomass polymers. Experiments in a semi-industrial pilot-scale system on wood boards allow to transpose the process towards real conditions. Similar to industry practices, the heating rate has been varied between 0.2 and 1.0°C min −1 . The results reveal noticeable differences in the degradation kinetics. A numerical tool has been tested to predict the advancement of the thermo-modification process. The observations are of interest for industrial applications.